The factors affecting job satisfaction: a case study among Bumitech Global Energy Sdn. Bhd. employees / Nur Shafini Mohd Said ... [et al.] - Mohd Said, Nur Shafini; Kamal, Nurul Adawiyah; Omar Ali, Siti Rapidah; Mat, Khalid Amin (Universiti Teknologi MARA, Perlis, 2020)
The purpose of this study is to highlight the factors affecting job satisfaction in Bumitech Global Energy Sdn. Bhd. Specifically, the study aimed to pursue the following objectives: to analyse the relationship between organizational safety and health, salary, relationship with co-workers and job satisfaction among employees in Bumitech Global Energy Sdn. Bhd. For the purposes of this study, the researcher selected Bumitech Global Energy Sdn. Bhd. as the population studied which includes 90 employees. A set of questionnaires was used as the main instrument for the purpose of data collection. A simple random sampling was selected from employees at Bumitech Global Energy Sdn. Bhd. for this study. The Pearson correlation coefficient and multiple regressions were used to classify factors that affect the satisfaction of employees at Bumitech Global Energy Sdn. Bhd. Statistical Package for Social Science (SPSS) was used for data analysis. The findings showed that relationship and cooperation with co-worker played an important role in job satisfaction. The hypothesis was accepted based on the findings. Management should pay full attention to paying the employees’ contribution satisfactorily. They should also be concerned about the provision of additional benefits for employees, in particular financial benefits. The researcher hopes that the results will also benefit the organization.